How Risky Is the Stock Market Right Now? Technical Analysis of 30 US Stocks - Bansal, Sagar; Bansal, Jyoti (Global journal of Business and Integral Security, 2024)
This paper discusses, how risky the stock market, currently is. The study does so by conducting a technical analysis of all 30 stocks in the Dow Jones Industrial Average Index (DJIA). Utilizing data up to October 15, 2024, and employing techniques such as chart pattern analysis, price channel analysis, and divergence analysis, the stocks were classified into three clusters: buying, selling, and neutral. The findings reveal that 8 stocks fall into the buying cluster, 11 into the selling cluster, and 11 are neutral. The results suggests that while certain stocks may experience declines, the overall market does not exhibit signs of an imminent crash and there is no need to panic at the present moment. The US stock-market appears balanced despite previous significant gains and challenges at a macro-economic level. Investors are advised to focus on individual stock rather than a broader portfolio level management to maange risk effectively.